Apoptotic Protease Activating Factor-1 Inhibitor Mitigates Myocardial Ischemia Injury via Disturbing Procaspase-9 Recruitment by Apaf-1. (27th November 2017) - Wang, Ying; Zhang, Qiuyan; Zhong, Liangjie; Lin, Mingshen; Luo, Xiaoling; Liu, Siyu; Xu, Peng; Liu, Xinhua; Zhu, Yi Zhun
Abstract : (2S, 3S, 4S, 5R, 6R)-6-(4-((4-guanidinobutoxy)carbonyl)-2, 6-dihydroxyphenoxy)-3, 4, 5-trihydroxytetrahydro-2H-pyran-2-carboxylic acid (ZYZ-488) was discovered as a novel inhibitor of apoptotic protease activating factor-1 (Apaf-1). In present work, a surface plasmon resonance (SPR) assay confirms the direct binding between ZYZ-488 and Apaf-1 and this interaction was found to be able to block the recruitment of procaspase-9 by Apaf-1. This study also shows that the treatment of MI (myocardial infarction) mice with this novel Apaf-1 inhibitor remarkably reduces the infarct size, improves cardiac functions, and attenuates the histopathology changes caused by MI. Meanwhile, here it is shown that ZYZ-488 decreases myocardial enzyme release, inhibits cardiomyocyte apoptosis, and suppresses the activation of the downstream cascade of caspases. Moreover, in silico prediction validated the drug-like properties of ZYZ-488. In conclusion, our findings present the first piece of evidence indicating the interaction between Apaf-1 and procaspase-9 as a novel therapeutic target in myocardial infarction and suggesting ZYZ-488 as a promising therapeutic option for myocardial infarction disease.